The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1136/bmjopen-2018-021675
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress disorder in UK civilians with traumatic brain injury: an observational study of TBI clinic attendees to estimate PTSD prevalence and its relationship with radiological markers of brain injury severity

Abstract: ObjectivesTo estimate the prevalence of post-traumatic stress disorder (PTSD) in a large civilian population with traumatic brain injury (TBI), and to assess whether brain injury severity is correlated with PTSD symptoms.DesignObservational, cross-sectional study.Setting and participantsOutpatient clinic in a major UK trauma centre and secondary care hospital. Estimates of PTSD prevalence are based on 171 sampled individuals attending TBI clinic within an 18-month period. Analysis of the relationship between T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…In a meta-analysis, Ophuis et al identified post-traumatic stress one year after any physical trauma in 16 to 27% of victims [ 22 ]. Qureshi et al found PTSD in 21% of patients 18 months after a head injury [ 23 ]. Finally, two meta-analyses found a prevalence of post-traumatic stress ranging from 3.7 to 60%, two years after a natural disaster [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis, Ophuis et al identified post-traumatic stress one year after any physical trauma in 16 to 27% of victims [ 22 ]. Qureshi et al found PTSD in 21% of patients 18 months after a head injury [ 23 ]. Finally, two meta-analyses found a prevalence of post-traumatic stress ranging from 3.7 to 60%, two years after a natural disaster [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the neuropsychological and clinical characterization of veterans with a history of TBI is partly complicated by potential over-laying mood disorders either related to a relatively increased incidence of PTSD in this population (61,62), or mood symptoms that may co-occur with neurodegenerative diseases itself including AD and CTE, both of which have been reported to have prominent mood symptoms (19,(63)(64)(65)(66). Consistent with this literature, our head injury patients showed elevations in scales of depression and mood lability.…”
Section: Discussionmentioning
confidence: 99%
“…Stress is common to the experience of TBI (e.g., Qureshi et al, 2019). Cannon (1932) was one of the first academics to apply the concept of stress to homeostasis in humans (Romero, Dickens, & Cyr, 2008).…”
Section: Allostasis and Allostatic Loadmentioning
confidence: 99%